First language influence on second language performance: A study of common English grammatical errors among rural secondary school students - Abu Bakar, Kesumawati; Abdul Hamid, Nor Zakiah; Mat Awal, Norsimah; Jalaluddin, Nor Hashimah (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
As a second language in Malaysia, English is taught to all from the pre-school level until the fifth form of the secondary school. Even though the teaching and learning of English is carried out for several years, many students still fail to acquire the language successfully at the end of their schooling, which in turn jeopardizes their chances of future employment. After being exposed to the language for eleven years, students, particularly those from the rural areas, are found to be linguistically incompetent and unable to communicate successfully in the target language. The question now is why has this issue arisen. This paper attempts to share some insights into the issue of incompetency in English among rural secondary school students in Kulai, Johor. It reports an analysis of common errors made by three hundred second language learners in the acquisition of Subject-Verb Agreement, Tenses and Relative Pronouns. Using a combination of Norrish’s approach to conducting Error analysis and Contrastive Analysis, initial analysis of the common errors revealed syntactical intra-lingual interference from the first language. This paper will present a comparative linguistic analysis of the syntactical structures of the two languages in our attempt to explain and offer insights into learners’ difficulties in acquiring the target language.